Development of Self Access Internet Based English Module to Support Student Centred Learning (SCL) of Engineering Education - Azwin Arif, Abdul Rahim; Nor Yazi, Khamis; Mohammad Musab, Azmat Ali; Mohd Shafeirul Zaman, Abd Majid; Supyan, Hussin; Mohamed Amin, Embi (Canadian Center of Science and Education, 2014)
This study describes the development of a self access internet based English module to support Student Centred Learning (SCL) of Engineering Education. The study presents two out of three cyclical stages of a developmental reseach approach, the Needs Analysis and Design and Development of the module. The learners’ need was determined from 63 engineering undergraduates learning styles and used in information presentations and selections of learning activities for the module. The module development was structured according to ADDIE Instructional Design Model. Three learning theories, behaviourist, cognitivist and particularly constructivist were used in designing the module User Interface (UI). The integration of technology to foster learners’ active engagement in SCL environment implicates a concrete need of ESL educators’ technological competence; thus, an emphasis on technology driven continuous professional development is advocated.